Cascaded Fresnel digital hologram and its application to watermarking - Deng, Shaogeng; Liu, Liren; Lang, Haitao; Zhao, Dong; Liu, Ximin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
A cascaded Fresnel digital hologram (CFDH) is proposed, together with its mathematical derivation. Its application to watermarking has been demonstrated by a simulation procedure, in which the watermark image to be hidden is encoded into the phase of the host image. The watermark image can be deciphered by the CFDH setup, the reconstructed image shows good quality and the error is almost close to zero. Compared with previous technique, this is a lensless architecture which minimizes the hardware requirement, and it is used for the encryption of digital image.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 413-420
Keywords: optyka; Fresnel digital holography; encryption and decryption; watermarking; image processing